Answer:
11
Step-by-step explanation:
This is because 11-1=10
Answer:
13a+27
Step-by-step explanation:
8a+12+5a+15= 13a+27
Answer:
![g(x) = 12 {e}^{ - x - 7}](https://tex.z-dn.net/?f=g%28x%29%20%3D%2012%20%7Be%7D%5E%7B%20-%20x%20-%207%7D%20)
Step-by-step explanation:
The parent function is
![g(x) = e {}^{x}](https://tex.z-dn.net/?f=g%28x%29%20%3D%20e%20%7B%7D%5E%7Bx%7D%20)
First it is asked to reflect over the y axis so using the rule
![g(x) = g( - x)](https://tex.z-dn.net/?f=g%28x%29%20%3D%20g%28%20-%20x%29)
Our function looks like
![g(x) = e {}^{ - x}](https://tex.z-dn.net/?f=g%28x%29%20%3D%20e%20%7B%7D%5E%7B%20-%20x%7D%20)
Then we are asked to shift the equation to the right 7. When shifting to the right or move the x axis, instead of adding 7 we would want to subtract 7 since the x axis is the independent variable and we must respect the y axis which is the dependent so using the rule
![g(x) = g(x - h)](https://tex.z-dn.net/?f=g%28x%29%20%3D%20g%28x%20-%20h%29)
When subtracting a 7 it looks like now
where h is the number we move . Now we are asked to apply a vertical stretch of 12. Since vertical stretch refers to the y axis, we are just going to multiply the function by 12 using the rule
![g(x) = a \times g(x)](https://tex.z-dn.net/?f=g%28x%29%20%3D%20a%20%5Ctimes%20g%28x%29)
where a is the vertical stretch. So now it would look like
![g(x) = 12 {e}^{ - x - 7}](https://tex.z-dn.net/?f=g%28x%29%20%3D%2012%20%7Be%7D%5E%7B%20-%20x%20-%207%7D%20)
I think its 0.156 because / means division